Pengembangan Calligraphy on Leaf Skeleton Sebagai UMKM Pendukung Wisata Religi Kudus Berbasis Gusjigang - Sulasfiana Alfi Raida; Mulyaningrum Lestari; Ita Rakhmawati; Hani Hiqmatunnisa; Ratih Listya Raharjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Calligraphy is a work of art that is in demand by many people as a means of increasing faith and piety. In Kudus there is a community of calligraphy activists from the Asy Syauq community. The media commonly used is paper, and sometimes canvas. One of the innovative media that can be used as a means to convey calligraphic works of art is the leaf frame. This work of calligraphy art on leaf skeleton media has the potential to be developed into a product for MSMEs in the Kudus. This is because Kudus is a religious tourist city with many visitors from various regions. This service is carried out by providing assistance to the Asy Syauq calligrapher community to develop Calligraphy on Leaf Skeleton and providing assistance to developing MSMEs that support religious tourism in the District. Kudus by applying Gusjigang business ethics. The Asy Syauq calligrapher community carried out the marketing results as MSMEs are starting to attract interest from various groups. Thus, there is a need for further dedication to developing MSMEs to further support religious tourism in the Kudus.